2017
DOI: 10.1039/c7ra10550a
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different β-nucleation agents on poly(l-lactic acid): structure, morphology, and dynamic mechanical behavior

Abstract: The WBG-II and TMB-5000 are both effective nucleating agents, which not only can enhance the crystallization rate, but also alter the packing structure of PLLA chain in the crystals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 48 publications
1
15
0
Order By: Relevance
“…However, in the po-PLA and ha-PLA fibers diffraction patterns, new peaks appeared in the range of 2θ ≈ 23–32° while diffraction peaks corresponding to the α structure are not clearly observed; only in the case of po-PLA a very weak diffraction peak is shown at 2θ = 16.7° (200). In Figure 7 B, which is the amplification of the 2θ ≈ 23–32° range, it is clearly observed that these new diffraction peaks appearing at 2θ ≈ 25.8 and 26.3° for po-PLA and at 2θ ≈ 25.8, 26.3 and 28.1° for ha-PLA, corresponding to the β crystalline form [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, in the po-PLA and ha-PLA fibers diffraction patterns, new peaks appeared in the range of 2θ ≈ 23–32° while diffraction peaks corresponding to the α structure are not clearly observed; only in the case of po-PLA a very weak diffraction peak is shown at 2θ = 16.7° (200). In Figure 7 B, which is the amplification of the 2θ ≈ 23–32° range, it is clearly observed that these new diffraction peaks appearing at 2θ ≈ 25.8 and 26.3° for po-PLA and at 2θ ≈ 25.8, 26.3 and 28.1° for ha-PLA, corresponding to the β crystalline form [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…PLLA spectra exhibits a broad absorption peak in the range 3700-3600 cm −1 which is assigned to ν(O-H) vibration modes. Hydrogen association can easily occur in hydroxyl groups, resulting in a shift of the corresponding absorption peak to lower wavenumbers and a gradual widening with the increase of the association degree [21]. Furthermore, the two peaks at about 2951 and 3003 cm −1 correspond to the ν(C-H) vibration modes of methyl groups.…”
Section: Synthesis and Characterization Of Block Copolymersmentioning
confidence: 99%
“…[ 56 ] Also, the PLLA IR spectrum exhibit characteristic bands attributable to CH stretch at 2998 and 2950 cm −1 , CO stretch at 1765 cm −1 , CO stretching vibration at 1100 cm −1 . [ 57–59 ]…”
Section: Resultsmentioning
confidence: 99%
“…[56] Also, the PLLA IR spectrum exhibit characteristic bands attributable to C-H stretch at 2998 and 2950 cm −1 , C=O stretch at 1765 cm −1 , C-O stretching vibration at 1100 cm −1 . [57][58][59] The IR spectrum of the PCL-b-PLLA diblock copolymer shown in Figure 4 exhibits a prominent band at 1758 cm −1 corresponding to C=O stretch for the PLLA segment and a shoulder band at 1728 cm −1 arising from the PCL block of the copolymer. The spectrum shows a clear shift in the absorption band values as compared to pristine PLLA and PCL which is in accordance with the reported literature.…”
Section: Ftir Of Pcl-b-plla Diblock Copolymermentioning
confidence: 99%